Neuronal upregulation of Prospero protein is driven by alternative mRNA polyadenylation and Syncrip-mediated mRNA stabilisation - Samuels, TJ; Arava, Y; Järvelin, AI; Robertson, F; Lee, JY; Yang, L; Yang, C-P; Lee, T; Ish-Horowicz, D; Davis, I (Company of Biologists, 2020)
During Drosophila and vertebrate brain development, the conserved transcription factor Prospero/Prox1 is an important regulator of the transition between proliferation and differentiation. Prospero level is low in neural stem cells and their immediate progeny, but is upregulated in larval neurons and it is unknown how this process is controlled. Here, we use single molecule fluorescent in situ hybridisation to show that larval neurons selectively transcribe a long prospero mRNA isoform containing a 15 kb 3' untranslated region, which is bound in the brain by the conserved RNA-binding protein Syncrip/hnRNPQ. Syncrip binding increases the mRNA stability of the long prospero isoform, which allows an upregulation of Prospero protein production. Adult flies selectively lacking the long prospero isoform show abnormal behaviour that could result from impaired locomotor or neurological activity. Our findings highlight a regulatory strategy involving alternative polyadenylation followed by differential post-transcriptional regulation.